Dyslexia : A Very Short Introduction - Snowling, Margaret J. (New York Oxford University Press, 2019)
Dyslexia is gaining increasing recognition as a relatively common learning disorder. Margaret Snowling introduces the exciting research surrounding dyslexia, considering potential causes, the neuroscience behind it and attempts to understand how it works, and the various strategies and interventions which can help people with dyslexia today.
Include Illustrations, References and Index
Keywords: Dyslexia